ANALISIS FAKTOR YANG MEMENGARUHI MAHASISWA DALAM MEMILIH PROGRAM STUDI PENDIDIKAN BAHASA ARAB STAIN PEKALONGAN - _, Nalim (IAIN Pekalongan, 2012)
The awareness of the importance of a good qualified education is experienced by many people of various strata. This is evidenced by the increasing numbers of students who move on to higher education. As one of the educational institutions, STAIN Pekalongan is committed to continuously improving the quality of education and to accommodate the wishes of the stakeholders. One form of this commitment is to establish new courses namely Intensive Arabic Program. This research was completed to know how big the public interest was against the opening of this course and what the dominant factors that influence students in choosing the Arabic Studies Program of STAIN Pekalongan were. 16 variables were proposed to find out the reasons why the students chose PAI of STAIN Pekalongan. From the population of 104 students of Arabic Education, the researcher selected a sample of 70 students (respondents). The selection was done randomly comprising 51 students and 19 students of the second semester of the fourth semester. The gender proportion of respondents consisted of 49% male students and 51% female students. Based on the value of KMO MSA and Bartlet's test, it showed that of the 16 variables submitted, there were only 13 significant variables. Of those 13 variables, they were reduced into 5 main factors – the curriculum, the promotion, the quality of lecturer, the college status, and the location.